Terahertz Nanoprobing of Semiconductor Surface Dynamics - Choi, Geunchang; Bahk, Young-Mi; Kang, Taehee; Lee, Yoojin; Son, Byung Hee; Ahn, Yeong Hwan; Seo, Minah; Kim, Dai-Sik (AMER CHEMICAL SOC, 2017)
Most semiconductors have surface dynamics radically different from its bulk counterpart due to surface defect, doping level, and symmetry breaking. Because of the technical challenge of direct observation of the surface carrier dynamics, however, experimental studies have been allowed in severely shrunk structures including nanowires, thin films, or quantum wells where the surface-to-volume ratio is very high. Here, we develop a new type of terahertz (THz) nanoprobing system to investigate the surface dynamics of bulk semiconductors, using metallic nanogap accompanying strong THz field confinement. We observed that carrier lifetimes of InP and GaAs dramatically decrease close to the limit of THz time resolution (similar to 1 ps) as the gap size decreases down to nanoscale and that they return to their original values once the nanogap patterns are removed. Our THz narioprobing system will open up pathways toward direct and nondestructive measurements of surface dynamics of bulk semiconductors.
Keywords: CARRIER DYNAMICS; FIELD ENHANCEMENT; GAAS; RECOMBINATION; INP; PHOTOCONDUCTIVITY